Analisis Sanitasi Lingkungan Masyarakat di Kelurahan Tembilahan Kota Kabupaten Indragiri Hilir Provinsi Riau - Randika Clara Gita Yolanda; Nefilinda Nefilinda; Momon Dt Tanamir (Jurnal Ilmu Alam dan Lingkungan, 2023)
This research is motivated by environmental problems that occur in the community in Tembilahan Village, Indragiri Hilir Regency, Riau Province. The amount of waste that is dumped into the river, as well as the disposal of feces and household waste, especially in people who live around the river. This type of research is descriptive where the research only describes the facts found in the field without making changes to each research variable. The data collection technique was the first time the researcher made observations at the location, then distributed questionnaires to 71 respondents and took documentation related to the problem to be studied. The results of this study concluded that sanitation in Kelurahan Tembilahan city was in the fairly good category. However, many still throw garbage, washing waste, and fecal waste directly into the river. So that the risk of sanitation in the environment is in the high-risk category. Because polluted rivers pose various risks such as; environmental pollution, causing unpleasant odors, and the proliferation of bacteria and viruses that cause various diseases such as diarrhea, dengue fever, vomiting, and other diseases.